Alternative culture media and cold-drying for obtaining high biological value Arthrospira platensis (Cyanobacteria). Issue 3 (4th May 2021) - Bari, Elia; Cascino, Federico Castillo; Foglio, Luciano; Proietti, Lorenzo; Perteghella, Sara; Torre, Maria Luisa; Parati, Katia
ABSTRACT: Arthrospira platensis is a source of proteins, polysaccharides, polyunsaturated fatty acids (in tiny amounts) and phenolic components that give it different biological properties. The type of nutrients present in the culture medium can influence the microalga metabolism and, consequently, the growth, composition and content of nutrients, bioactive compounds and biological properties. In this work, A. platensis was cultivated in the laboratory using six culture media (Zarrouk as a standard medium, and Media 1–5), containing different nitrogen sources, and subsequently harvested and dried by freeze-drying or cold-drying. Medium 4, with KNO3 as nitrogen source, proved to optimize the productivity of A. platensis (with a maximum yield of 1.34 ± 0.08 g l –1, better than the Zarrouk medium), to maximize protein synthesis (up to 70% w/w) and to increase the antioxidant activity. Conversely, Medium 3, containing KNO3 and NH4 NO3, was the best to optimize carbohydrates and lipids (up to 30% w/w and 2% w/w, respectively). Both Media 3 and 4 were able to increase chlorophyll- a and carotenoid synthesis compared to the other tested media. Cold-drying has proved to be an excellent alternative to the more expensive lyophilization: the content of carotenoids and antioxidant components was better preserved. This research has shown that low-cost media and cold-drying can be a promising strategy for obtaining a high biological value product, usable in both the pharmaceutical and food sectors, reducing production times and costs.